1993
DOI: 10.1002/j.1460-2075.1993.tb06076.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the central pseudoknot in 16S rRNA is essential for initiation of translation.

Abstract: The postulated central pseudoknot formed by regions 9–13/21–25 and 17–19/916–918 of 16S rRNA of Escherichia coli is phylogenetically conserved in prokaryotic as well eukaryotic species. This pseudoknot is located at the center of the secondary structure of the 16S rRNA and connects the three major domains of this molecule. We have introduced mutations into this pseudoknot by changing the base‐paired residues C18 and G917, and the effect of such mutations on the ribosomal activity was studied in vivo, using a ‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 34 publications
2
53
0
Order By: Relevance
“…Previous studies have shown that mutation of the residue G917 significantly perturbs the translational activity of ribosomes (Brink et al 1993). This is consistent with our results using the specialized ribosome system (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that mutation of the residue G917 significantly perturbs the translational activity of ribosomes (Brink et al 1993). This is consistent with our results using the specialized ribosome system (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, it has been proposed that box C sequences, part of the nut-like elements and harboring the RNase III cleavage site, might mediate the formation of the universally conserved central pseudoknot of the 30S subunit (24). Mutational studies in the pseudoknot region revealed that the mutant ribosomes were impaired for in vivo translation (15,33), establishing the significance of the central pseudoknot to ribosome function. Formation of the universally conserved pseudoknot is believed to be preceded by another pseudoknot structure that involves base pairing of a U3 box A-like sequence between positions −104 and −122 of the 5 0 leader of 16S rRNA and NTs 14-31 and 916-918 of 16S rRNA (24).…”
Section: Discussionmentioning
confidence: 97%
“…At the other extremity of helix 27, the adjacent segment encompassing nucleotides 913-920 interacts with the loop of helix 1, forming helix 2, as described above, which creates the central pseudoknot of the 30S subunit. Mutations that disrupt the central pseudoknot destabilize the 30S subunit and impair subunit association, demonstrating the importance of the central pseudoknot for ribosome function (Brink et al 1993;Poot et al 1996). It had been suggested that the central pseudoknot is subject to conformational rearrangements involving alternate base pairings during protein synthesis (Kössel et al 1990;Leclerc and BrakierGingras 1991), but these rearrangements were not supported by mutagenesis experiments (Pinard et al 1993;Poot et al 1998).…”
Section: Discussionmentioning
confidence: 99%